The circulation of meaning in the news produced from the registration of video surveillance cameras in Argentina - Jesús Romero, Adrián (2021)
The article presents the possible displacements in the circulation of meaning from the conversion into news of events captured by video surveillance camera in Argentina. It focuses on the changes in scale and the projection reached by the senses present in the discourse of the information that refers to crimes. Following an analytical model, he identifies different stages that take the event from the private to the public sphere, from the local to the national scale, and form the neighbors of a medium-sized city to the metropolitan institutional enunciators. The proposed circulation segmentation structures the article and results from the analysis of the discourse practiced on a corpus composed of news published between November 30 and December 4, 2018. The interpretive exercise operates as a case study and is about an attempted femicide recorded by the video surveillance cameras of a comercial premises. This event originates the hipermedia circulation object of interpretation and it happened in the Argentine city of Villa María, located in the province of Córdoba, the geographic center of the county.